Dihydromyricetin Improves High‐Fat Diet‐Induced Hyperglycemia through ILC3 Activation via a SIRT3‐Dependent Mechanism. Issue 16 (28th June 2022) - Zhou, Jie; Hou, Pengfei; Yao, Yu; Yue, Jing; Zhang, Qianyong; Yi, Long; Mi, Mantian
Abstract : Scope: Previous studies indicate that dihydromyricetin (DHM) effectively improved glucose homeostasis and alleviated insulin resistance in population‐intervened trials, yet the underlying mechanism remains obscure. Methods and results: Wild‐type male mice and recombinase activating gene 1(Rag1) –/– mice (lacking adaptive immunity lymphocytes) are fed with control, high‐fat diet (HFD), or HFD+DHM diets for 8 weeks. DHM effectively protects HFD feeding mice against hyperglycemia by promoting group 3 innate lymphoid cells (ILC3s) cells proliferation and interleukin 22 (IL‐22) production. Furthermore, IL‐22 secretion induced by DHM increases the expression levels of the tight junction (TJs) molecules to protect the intestinal barrier integrity, thereby decreasing the level of lipopolysaccharides (LPS), an endotoxin that is involved in the regulation of chronic tissue inflammation and insulin resistance. In addition, silent mating‐type information regulation 2 homolog 3 (SIRT3) deficiency results in more serious obesity and intestinal barrier damage following HFD feeding and abolished DHM‐mediated increase in IL‐22 expression levels of ILC3 cells in SIRT3 knockout (SIRT3KO) mice. DHM reduces metabolic stress and enhances mitochondrial respiratory capacity to promote cell proliferation and IL‐22 secretion by activating SIRT3 in ILC3 cells Conclusions: DHM improves IL‐22 production of ILC3 cells and subsequently inhibits intestinal barrier dysfunction to alleviate hyperglycemia partially mediated by SIRT3. Abstract : Dihydromyricetin improves high‐fat diet‐induced hyperglycemia through ILC3 activation via a SIRT3‐dependent mechanism: dihydromyricetin alleviates intestinal dysfunction by promoting ILC3s proliferation and IL‐22 production via SIRT3 induced mitochondrial metabolism, thereby inhibits high‐fat diet‐induced diabetes.